Normalization of puberty and adult height in girls with Turner syndrome: results of the Swedish Growth Hormone trials initiating transition into adulthood - Kriström, Berit; Ankarberg-Lindgren, Carina; Barrenäs, Marie-Louise; Nilsson, Karl Olof; Albertsson-Wikland, Kerstin (Frontiers in Endocrinology, 2023)
Objective: To study impact of GH-dose and age at GH-start in girls with Turner Syndrome (TS), aiming for normal height and age at pubertal onset (PO) and at adult height (AH). However, age at diagnosis will limit treatment possibilities. Methods: National multicenter investigator-initiated studies (TNR 87-052-01, TNR 88-072) in girls with TS, age 3-16yrs at GH-start during year 1987-1998, with AH in 2003- 2011. 144 prepubertal girls with TS, 132 girls followed to AH (Intention-To-Treat), while 43 girls reduced dose or stopped treatment prematurely, making n=89 for Per Protocol population. Age at GH-start were 3-9yrs (young; n=79) or 9-16yrs (old; n=53), treatment given recombinant human (rh)GH (Genotropin® Kabi Peptide Hormones, Sweden) 33 or 67 µg/kg/day, oral ethinyl-estradiol (2/3) or transdermal 17β-estradiol (1/3), and after age 11yrs mostly oxandrolone. Gain in heightSDS, AHSDS, age at PO and at AH were evaluated. Results: At GH-start, heightSDS was -2.8 (versus non-TS girls) for all subgroups, mean age for young 5.7yrs and old 11.6yrs. There was a clear dose-response in both young and old TS-girls, mean difference(95%CI) 0.66(-0.91 to -0.26), 0.57(-1.0 to -0.13), respectively. The prepubertal gainSDS (1.3 to 2.1) was partly lost during puberty (-0.4 to -2.1). Age/heightSDS at PO ranged from 13yrs/-0.42 for GH67young to 15.2 yrs/-1.47 for GH33old. At AH, GH67old-group became tallest (17.2yrs; 159.9cm; -1.27 SDS, total gainSDS 1.55), compared to GH67young- group being least delayed (16.1yrs;157.1 cm; -1.73 SDS, total 1.08). Shortest were GH33young (17.3yrs; 153.7cm: -2.28 SDS, total gainSDS 0.53), and most delayed GH33old group, (18.5yrs:156.5cm; -1.82 SDS, total gainSDS 0.98). Conclusion: For both young and old TS-girls, there was a GH-dose growth response, and for the young less delayed age at start of puberty and at AH. All four groups reached an AH within normal range, despite partly losing the prepubertal gain during puberty. Depending on age at diagnosis, low age at start with higher GH-dose resulted in greater prepubertal height gain, permitting estrogen start earlier at normal age and attaining normal AH at normal age, favoring physiological treatment and possibly also bone health, uterine growth and fertility, psychosocial wellbeing during adolescence, and the transition to adulthood.